Low Radon Cleanroom for Underground Laboratories - Ivan Štekl; Jirí Hůlka; Fadahat Mamedov; Pavel Fojtík; Eva Čermáková; Karel Jílek; Miroslav Havelka; Rastislav Hodák; Miroslav Hýža (Frontiers Media S.A., 2021)
Aim of a low radon cleanroom technology is to minimize at the same time radon, radon decay products concentration and aerosol concentration and to minimize deposition of radon decay products on the surfaces. The technology placed in a deep underground laboratory such as LSM Modane with suppressed muon flux and shielded against external gamma radiation and neutrons provides "Zero dose" space for basic research in radiobiology (validity of the LNT hypothesis for very low doses) and for the fabrication of nanoelectronic circuits to avoid undesirable "single event effects." Two prototypes of a low radon cleanroom were built with the aim to achieve radon concentration lower than 100 mBq·m3 in an interior space where only radon-free air is delivered into the cleanroom technology from a radon trapping facility. The first prototype, built in the laboratory of SÚRO Prague, is equipped with a standard filter-ventilation system on the top of the cleanroom with improved leakproofness. In an experiment, radon concentration of some 50 mBq·m−3 was achieved with the filter-ventilation system switched out. However, it was not possible to seal the system of pipes and fans against negative-pressure air leakage into the cleanroom during a high volume ventilation with the rate of 3,500 m3·h−1. From that reason more sophisticated second prototype of the cleanroom designed in the LSM Modane uses the filter-ventilation system which is completely covered in a further improved leakproof sealed metal box placed on the top of the cleanroom. Preliminary experiments carried out in the SÚRO cleanroom with a high radon activity injection and intensive filter-ventilation (corresponding to room filtration rate every 13 s) showed extremely low radon decay products equilibrium factor of 0.002, the majority of activity being in the form of an "unattached fraction" (nanoparticles) of 218Po and a surface deposition rate of some 0.05 mBq·m−2·s−1 per Bq·m−3. Radon exhalation from persons may affect the radon concentration in a low radon interior space. Balance and time course of the radon exhalation from the human body is therefore discussed for persons that are about to enter the cleanroom.